Looking for value in garbage: intervention in domestic solid waste management - Meneses La Riva, Mónica Elisa (2019)
The objective was to determine the effects of the intervention in the management of domestic solid waste for reuse, with the aim of reducing the environmental impact in the district of Los Olivos. The approach was quantitative, descriptive, quasi-experimental design. The population consisted of 40 families from a condominium in the north of Lima who were trained with 12 educational sessions on solid waste management. The participatory mechanism used was the intervention of a program that managed the reuse of domestic solid waste, which involved citizen participation in the municipal waste management process in order to reduce environmental impact and improve citizen awareness. The instrument used was an 11 question questionnaire on the level of knowledge about solid waste that it categorizes as adequate, moderately adequate and inadequate. Likewise, for the collection indicators, information from the SIGERSOL 2017 system was used, based on current regulations (paper, plastics, glass, and organic waste). The data collection techniques were direct observation and survey, respecting ethical considerations. The results demonstrated the effects of educational intervention in the management of domestic solid waste, and serves as a sustainable cooperation strategy within municipal environmental policies. It is concluded that the educational intervention plays a predominant role in the creation of responsibility, conscience and commitment of the citizens, thus developing a culture of care of the environment in the community. Hence the importance of educating and promoting good practices in the management of domestic solid waste to preserve the environment and improve the quality of life of the community.